The management of large congenital liver cysts. Issue 683 (September 1982) - Rashed, A.; May, R. E.; Williamson, R. C. N.
Abstract : Congenital solitary cysts of the liver seldom exceed 10 cm in diameter. Four such cases were seen over a 5-year period in a city with a catchment population of about 800, 000. One of these cysts was asymptomatic, but the others were complicated by intracystic haemorrhage, probable perforation and cyst-enteric fistula. Pre-operative liver scans and findings at laparotomy indicated a different treatment in each case—observation, aspiration, enucleation and drainage.